Literary Base of Historical and Pedagogical Researches of the Western region of Ukraine - Strazhnikova, Inna (Pedagogical Discourse, 2013)
In the article the author exposes the drastic changes of scientific paradigms in the world historiography, grounds the topicality of researches on historiographical problems, proves that problematic historiographical research activates the effort of modern scientists, speeds up more profound study of historical and pedagogical issues, allows to define the most effective way of their decision that needs a profound analysis and bringing in new sources.